2023
DOI: 10.1007/s00066-023-02091-9
|View full text |Cite
|
Sign up to set email alerts
|

Radiosurgery for ventricular tachycardia (RAVENTA): interim analysis of a multicenter multiplatform feasibility trial

Abstract: Background Single-session cardiac stereotactic radiation therapy (SBRT) has demonstrated promising results for patients with refractory ventricular tachycardia (VT). However, the full safety profile of this novel treatment remains unknown and very limited data from prospective clinical multicenter trials are available. Methods The prospective multicenter multiplatform RAVENTA (radiosurgery for ventricular tachycardia) study assesses high-precision image-gu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…In 2017, Cuculich et al [106] published their experience with five patients treated with single-fraction SBRT (25 Gy), with a 99.9% reduction in tachycardia episodes in the following 46 months. Data from the RAVENTA trial also support this approach in a further report on its safety [107].…”
Section: Heart Diseasementioning
confidence: 79%
“…In 2017, Cuculich et al [106] published their experience with five patients treated with single-fraction SBRT (25 Gy), with a 99.9% reduction in tachycardia episodes in the following 46 months. Data from the RAVENTA trial also support this approach in a further report on its safety [107].…”
Section: Heart Diseasementioning
confidence: 79%
“…Meta-analysis of seven observational studies with a total of 61 patients showed that six months after STAR, the VT burden reduction was 92%, accompanied with an 86% reduction in the number of ICD shocks [62]. Several small prospective trials were recently published [63][64][65][66][67]. These studies primarily focused on safety and indicated that STAR has acceptable short-term toxicity with no significant concerns regarding acute cardiac toxicity.…”
Section: Management Of Ventricular Arrhythmias In Lung Cancer Patientsmentioning
confidence: 99%